Nocturnal selective pressures on the evolution of human musicality as a missing piece of the adaptationist puzzle - Varella, Marco Antonio Correa (Frontiers in Psychology, 2023)
Human musicality exhibits the necessary hallmarks for biological adaptations. Evolutionary explanations focus on recurrent adaptive problems that human musicality possibly solved in ancestral environments, such as mate selection and competition, social bonding/cohesion and social grooming, perceptual and motor skill development, conflict reduction, safe time-passing, transgenerational communication, mood regulation and synchronization, and credible signaling of coalition and territorial/predator defense. Although not mutually exclusive, these different hypotheses are still not conceptually integrated nor clearly derived from independent principles. I propose The Nocturnal Evolution of Human Musicality and Performativity Theory in which the night-time is the missing piece of the adaptationist puzzle of human musicality and performing arts. The expansion of nocturnal activities throughout human evolution, which is tied to tree-to-ground sleep transition and habitual use of fire, might help (i) explain the evolution of musicality from independent principles, (ii) explain various seemingly unrelated music features and functions, and (iii) integrate many ancestral adaptive values proposed. The expansion into the nocturnal niche posed recurrent ancestral adaptive challenges/opportunities: lack of luminosity, regrouping to cook before sleep, imminent dangerousness, low temperatures, peak tiredness, and concealment of identity. These crucial night-time features might have selected evening-oriented individuals who were prone to acoustic communication, more alert and imaginative, gregarious, risk-taking and novelty-seeking, prone to anxiety modulation, hedonistic, promiscuous, and disinhibited. Those night-time selected dispositions may have converged and enhanced protomusicality into human musicality by facilitating it to assume many survival- and reproduction-enhancing roles (social cohesion and coordination, signaling of coalitions, territorial defense, antipredatorial defense, knowledge transference, safe passage of time, children lullabies, and sexual selection) that are correspondent to the co-occurring night-time adaptive challenges/opportunities. The nocturnal dynamic may help explain musical features (sound, loudness, repetitiveness, call and response, song, elaboration/virtuosity, and duetting/chorusing). Across vertebrates, acoustic communication mostly occurs in nocturnal species. The eveningness chronotype is common among musicians and composers. Adolescents, who are the most evening-oriented humans, enjoy more music. Contemporary tribal nocturnal activities around the campfire involve eating, singing/dancing, storytelling, and rituals. I discuss the nocturnal integration of musicality’s many roles and conclude that musicality is probably a multifunctional mental adaptation that evolved along with the night-time adaptive landscape.